EDUKASI MEDIA SOSIAL SEBAGAI SOLUSI PENINGKATAN PENJUALAN UMKM ON’S COFFEE - Akbar Sulbahri, Rifani; Putri, Yuni Adinda; Rachmawati, Yuni; Arifin, Firmansyah; Putra, Dimas Pratama (Jurnal Abdimas Musi Charitas, 2024)
The advancement of information technology has transformed the business world from traditional to integrated digital platforms. Easy and fast access to information encourages people to engage more in online shopping through e-commerce. Businesses, including MSMEs, must leverage technology to survive and grow. Social media is one of the critical technologies, serving not only to boost sales but also as a marketing communication tool to build brand image and consumer loyalty. However, MSMEs like On's Coffee face challenges such as low educational background, limited entrepreneurial skills, and restricted access to information. Training was provided on audience segmentation strategies, targeted paid advertising, and interactive features such as polls and video content to address these issues. The program successfully enhanced partner understanding, inspired creative content development, and improved business profits by optimizing social media as an effective digital marketing platform.